Extracellular stimulation of VSIG4/complement receptor Ig suppresses intracellular bacterial infection by inducing autophagy. Issue 9 (1st September 2016) - Kim, Kwang H.; Choi, Beom K.; Kim, Young H.; Han, Chungyong; Oh, Ho S.; Lee, Don G.; Kwon, Byoung S.
ABSTRACT: VSIG4/CRIg (V-set and immunoglobulin domain containing 4) is a transmembrane receptor of the immunoglobulin superfamily that is expressed specifically on macrophages and mature dendritic cells. VSIG4 signaling accelerates phagocytosis of C3-opsonized bacteria, thereby efficiently clearing pathogens within macrophages. We found that VSIG4 signaling triggered by C3-opsonized Listeria (opLM) or by agonistic anti-VSIG4 monoclonal antibody (mAb) induced macrophages to form autophagosomes. VSIG4-induced autophagosomes were selectively colocalized with the intracellular LM while starvation-induced autophagosomes were not. Consistent with these results, the frequency of autophagosomes induced by infection with opLM was lower in VSIG4-deficient bone marrow-derived macrophages (BMDMs) than in WT BMDMs. Furthermore, when VSIG4 molecules were overexpressed in HeLa cells, which are non-macrophage cells, VSIG4 triggering led to efficient uptake of LM, autophagosome formation, and killing of the infected LM. These findings suggest that VSIG4 signaling not only promotes rapid phagocytosis and killing of C3-opsonized intracellular bacteria, as previously reported, but also induces autophagosome formation, eliminating the LM that have escaped from phagosomes. We conclude that VSIG4 signaling provides an anti-immune evasion mechanism that prevents the outgrowth of intracellular bacteria in macrophages.